Jakość żywności - atut konkurencyjności czy niewiadoma? - Gabryšová, Marie (Foodstuffs Quality - Competitive Strength Or Unknown Factor?, 2006)
Safe food is an important issue for the European Community. That is why one from the targets how to create integrated market is not only securing free foodstuffs trade, but also producing qualitatively better food. But the research results show that unfamiliarity with the problems of food quality influence the quality of life presenting the fact that consumers do not properly appreciate high-quality food and therefore it is low competitive.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 237-243